Effectiveness of Artificial Intelligence Implementation in Educational Services at Islamic Schools in East Java - Alim, Muhammad Syahrul; Umiyati, Sri; Wahyuni, Elli Setiyo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The Student Passport system in private schools of East Java represents an Artificial Intelligence (AI)-based educational service innovation positioned as the primary strategic instrument in school digital transformation. This service operates through integrated involvement of management, teachers, students, and parents to respond to modern educational needs dynamics. This research aims to analyze AI's effectiveness as a decision-support system in discipline management, academic efficiency improvement, health monitoring, and mapping sustainability determinants. The study employs descriptive qualitative methods with triangulation data collection techniques based on effectiveness theories by Sutrisno, Siagian, and Hasibuan. Research findings reveal AI functions effectively as the primary driver of school operations. In disciplinary aspects, the system provides objective data supporting real-time decision-making. In academic domains, AI serves as an intelligent assistant facilitating automated lesson planning preparation and mass exam correction, while also functioning as an information access gateway for students. System effectiveness extends to health services through predictive analysis features delivering medical information and preventive action recommendations for student welfare. Managerially, efficiency is demonstrated through paperless budget savings and accelerated information distribution. Success supporting factors include management commitment (top-down policy) and server infrastructure stability, while inhibiting factors comprise network capacity limitations (peak load bottlenecks) and low digital literacy among certain parents. The research concludes that schools have successfully established robust digital ecosystems but require network infrastructure strengthening and external user education to ensure Smart School sustainability.